A genome‐wide association study of sleep habits and insomnia12. Issue 5 (31st May 2013) - Byrne, Enda M.; Gehrman, Philip R.; Medland, Sarah E.; Nyholt, Dale R.; Heath, Andrew C.; Madden, Pamela A. F.; Hickie, Ian B.; Van Duijn, Cornelia M.; Henders, Anjali K.; Montgomery, Grant W.; Martin, Nicholas G.; Wray, Naomi R.; et al.
Abstract Several aspects of sleep behavior such as timing, duration and quality have been demonstrated to be heritable. To identify common variants that influence sleep traits in the population, we conducted a genome‐wide association study of six sleep phenotypes assessed by questionnaire in a sample of 2, 323 individuals from the Australian Twin Registry. Genotyping was performed on the Illumina 317, 370, and 610K arrays and the SNPs in common between platforms were used to impute non‐genotyped SNPs. We tested for association with more than 2, 000, 000 common polymorphisms across the genome. While no SNPs reached the genome‐wide significance threshold, we identified a number of associations in plausible candidate genes. Most notably, a group of SNPs in the third intron of the CACNA1C gene ranked as most significant in the analysis of sleep latency (P = 1.3 × 10−6). We attempted to replicate this association in an independent sample from the Chronogen Consortium (n = 2, 034), but found no evidence of association (P = 0.73). We have identified several other suggestive associations that await replication in an independent sample. We did not replicate the results from previous genome‐wide analyses of self‐reported sleep phenotypes after correction for multiple testing. © 2013 Wiley Periodicals, Inc.